Selected Topics on Perspectives in Business Informatics Research: Editorial Introduction to the Issue 14 of CSIMQ - Björn Johansson; Charles Møller (Complex Systems Informatics and Modeling Quarterly)
Globalization, abundant networking possibilities, and advances in artificial intelligence are creating a new business environment where cooperation and competition requires from enterprises high agility and ability to intelligently acquire, analyze, and apply their internal and external data. In this regard, several information system concepts must be reconsidered to adopt various opportunities offered by the new environment. The fourteenth issue of the journal “Complex Systems Informatics and Modeling Quarterly” (CSIMQ) offers a selection of papers addressing research perspectives that concern digital trade infrastructures, business process agility, and the quality of business intelligence tools. The initial versions of these papers were presented and discussed at the 16th International Conference on Perspectives in Business Informatics Research and its associated events on August 28–30, 2017 in Copenhagen, Denmark.